2016
DOI: 10.3382/ps/pev308
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of meat traits of Sussex cockerels and capons (S11) at different ages

Abstract: The aim of the study was to compare Sussex cockerels and capons as well as to estimate the influence of age on slaughter yield and meat quality. The tests were performed on cockerels and capons from strain S11 (Sussex). At 16, 18, and 20 wk of age, a dissection of the entire carcass was conducted. The breast and leg muscles were tested for physio-chemical traits, as well as chemical parameters. It was noted that, due to significant differences in BW of the eviscerated carcasses between wk 18 and 20 of slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The cockerels of the layer line or dual-purpose breeds are another suitable option. Moreover, caponisation is beneficial in these breeds, because the caponisation can increase the culinary quality of the meat [4,5] and bone strength [6] compared to cockerels. One-day-old male layers are usually culled directly after hatching due to their inefficient growth rate compared with broilers, which implies a long fattening period and unfavourable feed conversion [7].…”
Section: Introductionmentioning
confidence: 99%
“…The cockerels of the layer line or dual-purpose breeds are another suitable option. Moreover, caponisation is beneficial in these breeds, because the caponisation can increase the culinary quality of the meat [4,5] and bone strength [6] compared to cockerels. One-day-old male layers are usually culled directly after hatching due to their inefficient growth rate compared with broilers, which implies a long fattening period and unfavourable feed conversion [7].…”
Section: Introductionmentioning
confidence: 99%
“…Undesirable behavioral changes can be eliminated by surgical or chemical castration (Quaresma et al, 2017). Caponization is carried out to produce meat with exceptional flavor (Díaz et al, 2010; Calik et al, 2015; Adamski et al, 2016; Amorim et al, 2016). Previous research revealed increased deposition of fat in caponized birds, in particular abdominal fat and mesenteric fat, which can decrease carcass dressing percentage (Zawacka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the native Zk breed for production of capons has been investigated by few researchers (Calik et al 2015;Kwiecień et al, 2015;Adamski et al, 2016;Zawadzka et al, 2016;Gesek et al, 2017). As indicated in a study conducted by , Zk capons exhibited a beneficial weight gain of the breast muscle, increased content of fat (abdominal, intramuscular), and favourable changes in thigh muscles, i.e.…”
Section: Introductionmentioning
confidence: 99%